Expression of pinopodies in women with endometry hyperplasia without atipy and fertility disorders - Nosenko, E. N.; Golovatyuk, E. P.; Doroshenko, V. E.; Rutinskaya, A. V.; Parnitskaya, O. I. (Journal of Education, Health and Sport, 2017)
Non-atypical endometrial hyperplasia (EH) most often occurs against a background of relative or absolute hyperestrogenism, responds to abnormal hormonal effects. In the reproductive age, the presence of EH can be a factor in the development of fertility disorders. The aim of the study was to learn the expression of pinopodes in ovulatory infertile women with non-atypical EH on the day of the implantation window. Under observation there were 196 women of reproductive age, of which 166 had been treated for infertility, and 30 conditionally gynecologically and somatically healthy, fertile women of the control group. A special examination of women included the determination in the endometrium by scanning electron microscopy of pinopodes’ expression. It was found that in women with non-atypical hyperplasia of the endometrium, areas without pinopodia were recorded in 47.59% of cases, pinopodes of small size - in 79.52% and abundant, small, thick microvilli - in 37.95%; the decrease in the incidence of developed pineapods in comparison with healthy prolific women was 2.72 times, that of pinopodes of large size was 3.39 and the small number of microvilli was 3.64, an increase in the occurrence of pinopodes of medium size 3.65, microvilli in moderate amounts - at 3.74. The authors conclude that the characteristic feature of endometrial pinopodes in EH is the presence of mosaicism of their shape (60.24%), size (64.46%) and the presence of numerous areas of absence of pinopodes (47.59%), which plays a significant role in disorders fertility.